Correlates of continued cannabis use during pregnancy. (1st October 2021) - Pike, Chelsea K.; Sofis, Michael J.; Budney, Alan J.
Highlights: Certain factors predicted whether women continued or quit cannabis for pregnancy. Less perceived risk and more frequent use pre-pregnancy predicted continued use. The odds of continued cannabis use were increased with pre-pregnancy cigarette use. Being unemployed and in the first trimester of pregnancy predicted continued use. Content of discussions about cannabis with a doctor were associated with use status. Abstract: Background: Cannabis use is increasingly common among pregnant women despite concern that it may be linked to adverse maternal and infant outcomes. Determining whether variables associated with cannabis use predict whether women continue or quit using during pregnancy may inform strategies to reduce prenatal use. Methods: Pregnant women who regularly used cannabis before pregnancy ( n = 296) were recruited via Facebook. After finding out they were pregnant, 41 % reported quitting, 13 % quit then relapsed, 32 % reduced use, and 15 % continued use at the same rate. Differences among these four cannabis use status groups (quit, relapsed, reduced, continued) in sociodemographics, cannabis use, cigarette use, perceived risk/benefit, delay discounting, and communications about cannabis with their doctor were assessed. Results: Compared to those who quit, continuing use during pregnancy was associated with being unemployed (Relative Risk (RR) = .32, 95 %CI [.13, .78]), using cigarettes pre-pregnancy (RR = 3.43, 95 %CI [1.32, 8.94]), being in an earlier trimester (RR = 4.38, 95 %CI [1.18, 16.23]), less perceived risk (RR = .79, 95 %CI [.74, .85]), and more days per week of use pre-pregnancy (RR = .10, 95 %CI [.01, .84]). Unintended pregnancy, shorter time to cannabis use after waking pre-pregnancy, using cannabis more times per day pre-pregnancy, and greater perceived benefits of use had significant bivariate associations with continued use during pregnancy, but did not retain significance in a multinomial model. Conclusions: Identification of these correlates provides potential targets for prevention of or intervention for prenatal cannabis use. However, much more research is needed to understand prenatal cannabis use and its effects in order to better educate women and healthcare providers, and to design optimal public health strategies.